Did Output Recover From the Asian Crisis? - Cerra, Valerie (IMF Working Papers; Working Paper, 2003)
This paper investigates the extent to which output has recovered from the Asian crisis. A regime-switching approach that introduces two state variables is used to decompose recessions in a set of six Asian countries into permanent and transitory components. While growth recovered fairly quickly after the crisis, there is evidence of permanent losses in the levels of output in all of the countries studied.